Mitigating the Effects of De-Risking in Emerging Markets to Preserve Remittance Flows - Ramachandran, Vijaya (International Finance Corporation, Washington, DC, 2018)
Anti-money laundering and combating-the-financing-of-terrorism laws are grounded in reasonable national security concerns, preventing the cross-border flow of funds to terror or criminal groups. But these policies can have unintentional and costly consequences, in particular for people in poor countries. Those most affected are likely to include the families of migrant workers, small businesses that need to access working capital or trade finance, and recipients of life-saving aid in active-conflict, post-conflict or post-disaster situations.